Directors' duties : old principles, new perspectives - Ahern, Deirdre (Trinity College (Dublin, Ireland). School of Law, 2008)
In managing a company on behalf of the shareholders, directors are possessed of significant freedom. This freedom is constrained by the duties owed by directors to the company, duties which were initially developed by the courts in the nineteenth century by analogy with the duties of trustees. These duties are: -- (i) the duty to exercise due care, skill and diligence in the performance of their duties; -- (ii) the duty to act bona fide in the best interests of the company as a whole and for proper purposes; and -- (iii) the duty to avoid secret profits and conflicts of interest. This thesis assesses the extent to which these duties, and the principles which underpin them, have stood the test of time. As such it is a study of the application, durability and adaptability of the traditional non-statutory duties of directors. Of particular significance to this assessment is the Company Law Review Group’s recommendation that directors’ duties be placed on a statutory footing within a new unified company law legislative scheme. This resulted in the publication of a General Scheme of the Company Law Consolidation and Reform Billin May 2007, Part A5 of which is designed to move directors’ duties to a statutory footing. One of the major concerns with a codification of directors’ duties is the potential loss of flexibility.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin